A Delphi study on factors influencing school students’ adoption of social media as a learning platform in Malaysia - Abas, Imelda Hermilinda; Krishnamurthi, Nawanantiny; Rasli, Amran; Gusteti, Meria Ultra (International Journal of Evaluation and Research in Education (IJERE), 2025)
The increasing use of social media platforms among students offers potential for both academic and personal information exchange. However, the factors influencing its adoption for learning by school students remain underexplored. This study aims to identify and rank the key factors that affect the use of social media for learning among primary school students. Utilizing the Delphi method, data were collected in two rounds from 30 expert participants, who were primary school teachers, using purposive sampling. In the first round, thematic analysis identified six key factors influencing social media adoption. In the second round, these factors were ranked in order of importance, with Kendall’s W of 0.364 and a p-value of 0.000 confirming consensus. In addition, an intraclass correlation coefficient (ICC) value of 0.923 indicated reliability. The top three factors identified were learning transformation, technology reform, and long-term prospects for students. The findings suggest that schools should prioritize these factors in strategic planning. Future research could expand this study to include private and international educators, and qualitative studies like tracer research could further enrich the understanding of social media’s role in learning.